Research on tugboat scheduling optimization model considering the reliability of tugboat matching scheme - Yangjun Ren; Mengchi Li; Yushun Lei; Yan Zhou; Di Liu; Jianjun Tu; Botang Li (Scientific Reports)
Abstract The selection and scheduling of tugboat matching schemes are key tasks in tugboat assistance operation management. With large ships requiring more tugboat assistance, a two-stage multi-criteria decision-making method is proposed. This includes a normal distribution-based multi-attribute group decision-making method with triangular fuzzy numbers to determine tugboat matching scheme reliability. A tugboat scheduling planning model for multiple berthing bases is then established, targeting the minimization of total fuel cost and total matching scheme reliability. This bi-objective problem is solved using the posteriori method, with actual data from Nansha Port validating the proposed method. Meanwhile, a priority-based encoding Memetic algorithm is designed to address the characteristics of the problem, and the solution results for 25 test cases generated from the actual data range of the Guangzhou Port are compared and analyzed using CPLEX, genetic algorithms, and simulated annealing algorithms. The results verify the feasibility of the proposed priority-based encoding Memetic algorithm. The enhanced multi-attribute group decision-making method helps decision-makers quickly select suitable matching schemes and optimize tugboat scheduling, demonstrating effective reliability evaluation and planning optimization.